Age-Related Changes in Nanoparticle Albumin-Bound Paclitaxel Pharmacokinetics and Pharmacodynamics: Influence of Chronological Versus Functional Age. (9th December 2014) - Hurria, Arti; Blanchard, M. Suzette; Synold, Timothy W.; Mortimer, Joanne; Chung, Cathie T.; Luu, Thehang; Katheria, Vani; Rotter, Arnold J.; Wong, Carol; Choi, Anthony; Feng, Tao; Ramani, Rupal; et al.
Abstract: Purpose: This study evaluated age-related changes in pharmacokinetic and pharmacodynamic parameters of nanoparticle albumin-bound paclitaxel ( nab -paclitaxel) in patients with metastatic breast cancer. Methods: Forty patients received nab -paclitaxel (100 mg/m 2 weekly for 3 weeks followed by a 1-week break) as first- or second-line chemotherapy. Blood samples were collected for analysis, and response was assessed every two cycles. Planned statistical analyses included linear regression to examine the relationship between age and pharmacokinetic variables (ln clearance [CL] and ln area under the curve [AUC]) and two-sided two-sample t tests to evaluate age differences in pharmacodynamic variables. The association between chemotherapy toxicity risk scores and pharmacokinetic and pharmacodynamic variables including grade ≥3 toxicity were examined post hoc. Results: Of 40 patients enrolled, 39 (98%) were evaluable (mean age: 60 years; range: 30–81 years). A partial response was achieved in 31%, and 38% had stable disease. There was a borderline positive association between age and 24-hour ln AUC (slope = 0.011; SE = 0.006; p = .055). Grade 3 toxicity was experienced by 26% (8% hematologic, 18% nonhematologic). There were no differences in age based on the presence of grade 3 toxicity ( p = .75), dose reductions ( p = .38), or dose omissions ( p = .15). A significant association was noted between chemotherapy toxicity risk score category and presence of grade 3 toxicity (toxicity rate by risk score category: low, 5 of 30 patients; medium, 3 of 6 patients; high, 2 of 3 patients; p = .041). Conclusion: A borderline significant relationship exists between age and 24-hour AUC, but no differences were noted for pharmacodynamic variables (grade 3 toxicity, dose reductions, or dose omissions) based on age. There is an association between toxicity risk score and grade ≥3 chemotherapy toxicity and pharmacokinetic variables. The treatment is well tolerated across all age groups. Abstract : This study evaluated age-related changes in pharmacokinetic and pharmacodynamic parameters of nanoparticle albumin-bound paclitaxel in patients with metastatic breast cancer. A borderline significant relationship exists between age and 24-hour area under the curve, and there is an association between toxicity risk score and grade ≥3 chemotherapy toxicity and pharmacokinetic variables. The treatment is well tolerated across all age groups.